Systematic Literature Review: “Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Canva, Quizizz, dan Wordwall dalam Meningkatkan Keaktifan Siswa Sekolah Dasar” - putri, Natasya; Meisa Putri, Tisi; Rahmadani, Winda; Nisja Pratiwi, Delvina; Fitria, Yanti; Habibi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ activeness is currently considered a key indicator of learning achievement. However, the level of activeness among elementary school students remains relatively low, primarily due to the use of conventional teaching methods and the limited integration of technology in the classroom. This study aims to examine the improvement of elementary students’ activeness after the implementation of technology-based learning media such as Canva, Quizizz, and Wordwall.The methodology employed in this study is a Systematic Literature Review (SLR). The research process began with problem formulation, followed by article collection, screening based on inclusion and exclusion criteria, and analyzing as well as synthesizing the findings of each selected study. A total of 24 articles were included in this review after a rigorous screening process from an initial pool of 600 articles.The findings indicate that Canva, Quizizz, and Wordwall as learning media can effectively enhance the activeness of elementary school students during the learning process. Therefore, the use of Canva, Quizizz, and Wordwall can be considered an effective solution to improve students’ activeness in elementary education.